2013
DOI: 10.1128/iai.00418-13
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas aeruginosa Uses Multiple Pathways To Acquire Iron during Chronic Infection in Cystic Fibrosis Lungs

Abstract: dPseudomonas aeruginosa chronically infects the lungs of more than 80% of adult patients with cystic fibrosis (CF) and is a major contributor to the progression of disease pathology. P. aeruginosa requires iron for growth and has multiple iron uptake systems that have been studied in bacteria grown in laboratory culture. The purpose of this research was to determine which of these are active during infection in CF. RNA was extracted from 149 sputum samples obtained from 23 CF patients. Reverse transcription-qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
112
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(121 citation statements)
references
References 56 publications
8
112
0
Order By: Relevance
“…More recently, Martin et al (2011) showed that although pyoverdine was detectable in most P. aeruginosa infected CF sputa, some sputa were pyoverdine-negative (Martin et al, 2011). Consistent with these findings, Konings et al (2013) subsequently demonstrated using real-time quantitative PCR that genes associated with siderophore-mediated iron acquisition including pyoverdine and pyochelin are expressed at low levels in CF sputum, and both haem and ferrous iron uptake genes were also detected, indicating multiple iron uptake pathways are active but siderophore secretion is downregulated (Konings et al, 2013). This phenomenon was further explored by Andersen et al (2015) in a sequence analysis study which confirmed that in the CF lung environment, many P. aeruginosa strains 'cheat' by no longer producing pyoverdine and instead use pyoverdine produced by co-infecting strains (Andersen et al, 2015).…”
Section: Pathogen Interactions and Competition For Iron In Cfsupporting
confidence: 80%
“…More recently, Martin et al (2011) showed that although pyoverdine was detectable in most P. aeruginosa infected CF sputa, some sputa were pyoverdine-negative (Martin et al, 2011). Consistent with these findings, Konings et al (2013) subsequently demonstrated using real-time quantitative PCR that genes associated with siderophore-mediated iron acquisition including pyoverdine and pyochelin are expressed at low levels in CF sputum, and both haem and ferrous iron uptake genes were also detected, indicating multiple iron uptake pathways are active but siderophore secretion is downregulated (Konings et al, 2013). This phenomenon was further explored by Andersen et al (2015) in a sequence analysis study which confirmed that in the CF lung environment, many P. aeruginosa strains 'cheat' by no longer producing pyoverdine and instead use pyoverdine produced by co-infecting strains (Andersen et al, 2015).…”
Section: Pathogen Interactions and Competition For Iron In Cfsupporting
confidence: 80%
“…In line with this hypothesis, pyoverdine is present in the sputum of some but not all CF patients (31), and in one study, one-third of P. aeruginosa strains isolated from CF patients had lost the ability to produce pyoverdine (32). Additionally, expression of the genes for pyoverdine biosynthesis by P. aeruginosa growing in the CF lung is variable (33). Moreover, recent genome sequencing analysis of numerous CF isolates demonstrated the highest level of genetic diversity among infecting P. aeruginosa strains to be localized to the pyoverdine synthesis and uptake genes (34).…”
mentioning
confidence: 70%
“…In support of this idea, genes encoding the ferrous iron and heme uptake systems are consistently expressed by P. aeruginosa growing in the CF lung (33,35). P. aeruginosa acquires ferrous iron via the Feo system, a G-protein-like transporter of ferrous iron (36)(37)(38)(39), and mediates heme acquisition via at least two systems: Phu (Pseudomonas heme uptake) and Has (heme assimilation system) (40).…”
mentioning
confidence: 90%
“…To our knowledge, this is the first report of a microbial natural product that is a direct inhibitor of a competing species' siderophore transport system. Multiple studies have implicated the pyochelin siderophore system in virulence (74)(75)(76), including genetic abrogation of pyochelin-mediated iron uptake that diminished P. aeruginosa virulence in murine infection models (53,54). In this context, escherichelin-producing Enterobacteriaceae at colonized devices or mucosal surfaces may prevent P. aeruginosa from progressing to symptomatic infection by chemically inhibiting pyochelin-mediated iron uptake.…”
Section: Discussionmentioning
confidence: 99%